Congenital Syphilis Coinfection in a Preterm Infant with Early Onset Sepsis due to Enterobacter cloacae - Sakviseth Bin; Sethikar Im (Case Reports in Infectious Diseases)
Introduction. Syphilis is a tropical disease, caused by a spirochete Treponema pallidum, which can be transmitted transplacentally from untreated mothers to the fetus during any stages of pregnancy. Clinical manifestations of early congenital syphilis are variable and nonspecific. The diagnosis is based on the serology status of the mother, newborn clinical symptoms, and comparative serology titer between mother and newborn. Case Presentation. A late preterm female infant, appropriate for gestational age, was treated for severe early onset sepsis due to Enterobacter cloacae since day 2 of life. The coinfection with Treponema pallidum was suspected and confirmed at day 4 with clinical signs and a fourfold increase of rapid plasma reagin (RPR) compared to mother’s serology. Combined with meropenem and amikacin, Benzyl-Penicillin was used for 10 days, thereby resulting in a significant clinical and laboratory improvement. The girl was discharged at day 18 and brought for regular follow-ups for both growth milestone and syphilis serology. RPR decreased fourfold at the age of 1 month. Conclusion. Syphilis should not be overlooked. The vertical transmission is preventable by an on-time treatment of the infected mother, triggered by a proper antenatal screening at the right time. Congenital syphilis should be ruled out in any challenging neonatal sepsis. The diagnosis tools and treatments are easily accessible and inexpensive in our economical settings.